FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENYEMBUHAN PENYAKIT TB PARU DI PUSKESMAS SEI BAUNG KOTA PALEMBANG TAHUN 2020 - Susiyanti, Susiyanti; Juniastra, Muhammad Riqqi; Sigalingging, Jasminten; Irdan, Irdan (JURNAL KESEHATAN TERAPAN, 2020)
Lung TB is a contagious infectious disease caused by Mycobactrium Tubeculosis. The government has implemented a strategy of treating tuberculosis for 6-8 months to eradicate this disease. However, there are factors associated with curing pulmonary TB, including: education, knowledge, social status, economy, nutritional status, population density, and distance from health centers. Based on data and observations from pulmonary TB patients actively seeking treatment at the Sei Baung Health Center in Palembang in 2022, there were 40 patients in the treatment phase last year. The purpose of this study was to determine the factors linked to the cure from pulmonary tuberculosis at the Sei Baung Health Center in Palembang in 2022. The place of this research was done at Sai Baung Health Center in Palembang City. The design of this research is to be an analytical survey with a cross-sectional approach, in which the independent and dependent variables are collected simultaneously with a total sample of 40 people with the general population. The data was collected through questionnaires, interviews and medical records from the health center. The results showed that there was a significant association between the attitude variable (p-value: 0.004) and knowledge (p-value: 0.03) about the cure for pulmonary tuberculosis at the Sei Baung Health Center in Palembang in 2022. The conclusion of this study is that there is a significant relationship between There is a significant relationship between attitudes and pulmonary TB disease and there is a significant relationship between knowledge and pulmonary TB disease. This research suggests that in providing quality health services, it is better to improve the provision of information and there is hope that access to health services can be improved, especially with regard to pulmonary TB diseases.